Nobiletin Ameliorates Cellular Damage and Stress Response and Restores Neuronal Identity Altered by Sodium Arsenate Exposure in Human iPSCs-Derived hNPCs - Sadaf Jahan; Uzair Ahmad Ansari; Arif Jamal Siddiqui; Danish Iqbal; Johra Khan; Saeed Banawas; Bader Alshehri; Mohammed Merae Alshahrani; Suliman A. Alsagaby; Neeru Singh Redhu; Aditya Bhushan Pant (MDPI AG, 2022)
Environmental exposure to arsenic has been profoundly associated with chronic systemic disorders, such as neurodegeneration, in both experimental models and clinical studies. The neuronal cells of the brain and the nervous system have a limited regeneration capacity, thus making them more vulnerable to exposure to xenobiotics, leading to long-lasting disabilities. The functional and anatomical complexity of these cells hinders the complete understanding of the mechanisms of neurodegeneration and neuroprotection. The present investigations aimed to evaluate the neuroprotective efficacy of a herbal formulation of Nobiletin (NOB) against the toxic insult induced by sodium arsenate (NA) in human neural progenitor cells (hNPCs) derived from human induced pluripotent stem cells (hiPSCs). Prior to the neuroprotective experiments, biologically safe doses of both NOB and NA were ascertained using standard endpoints of cytotoxicity. Thereafter, the hNPCs were exposed to either NOB (50 μM) or NA (50 μM) and co-exposed to biologically safe concentrations of NA (50 μM) with NOB (50 μM) for a period of up to 48 h. NOB treatment restored the morphological damage (neurite damage), the levels of stress granule G3BP1 (Ras-GTPase-activating protein (SH3 domain)-binding protein) and TIA1 (T cell-restricted intracellular antigen), and the expression of neuronal markers (Tuj1, Nestin, MAP2, and PAX6) when compared to NA-exposed cells. A substantial restoration of reactive oxygen species and mitochondrial membrane potential was also witnessed in the co-exposure group (NA + NOB) in comparison to the NA-exposed group. The findings suggest that NOB possesses a significant restorative/protective potential against the NA challenge in hNPCs under experimental conditions and imply that nobiletin may impart a potential therapeutic impact if studied adequately using in vivo studies.